EFFECT OF CYNAMMYLDEHYDE FROM CINNAMON EXTRACT AS A NATURAL PRESERVATIVE ALTERNATIVE TO THE GROWTH OF Staphylococcus aureus BACTERIA - Winias, Saka (Institute of Topical Disease Universitas Airlangga, 2011)
Food is one of the best media for the microorganism to live and grow. Therefore, food is often broken because it has been contaminated by the microorganism. In industry country, approximately 30% of population infected by food borne disease. Food borne disease is caused of phatogen bacteria food borne. Staphylococus aureus is a kind of bacteria that can make food rotten and also it is a phatogen bacteria cause food born disease, no forming spora, positive gram bacteria and the food substance which is contaminated by Staphylococus aureus will cause poisoned becaused of enterotoxin which is heat resisting. Essential oil is antimicrobial and anti bacterial that the most effective, it can inhibit the growing of microba and bacteria. One of the example of essential oil is Cinnamon.sp oil. Cinnamon oil is antimcroba agent for bacteri and fungi because it contain cynammyldehyde and cynammyl alcohol and also eugenol. The aim of this study is to understand the antimcrobacterial potential of cynammyldehyde from cinnamon extract to Staphylococus aureus. This study is laboratory experimantal research. Essential oil from Cinnamon by destilation, then redistilation was done to get cynammyldehyde from cinnamon. Cynammyldehyde was tested to Staphylococus aureus. Test method was done as dilution in the form. From this result, it show that cynammyldehide from cinnamon extract has ability in inhibit the Staphylococus aureus growth. We can conclude that Cynammaldehyde from cinnamon extract has antibacterial effect especially for positive gram bacteria that is Staphylococcus aureus. The optimum inhibiting effort is 0.09%.